Design and Implementation of a Digital Project-Based Learning Framework for Electrical Circuit Laboratory Instruction - Ade Irfansyah; Bambang Bagus; Yuyun Suprapto; Nyaris Pambudi; Teguh Imam Suharto; Achmad Setiyo Prabowo (Universitas Trunodjoyo Madura, 2025)
Electrical circuit instruction in aviation vocational education faces persistent challenges, including limited laboratory infrastructure, conventional teaching methods, and low student engagement. This study developed an instructional module based on Project-Based Learning (PjBL), integrated with a Learning Management System (LMS) and mockup trainers, using the ADDIE model through its Analysis, Design, and Development phases. The module comprises a semester learning plan (RPS), LMS-based digital content, practical mockups, and rubric-based project assessments. Expert validation confirmed the module’s technical feasibility, media quality, and pedagogical relevance, with scores of 83% from the electrical engineering expert, 80% from the media expert, and 85% from the instructional technology expert. These results affirm the module’s readiness for implementation in vocational education. The study underscores the value of contextual digital instructional design in bridging theory and practice, enhancing student motivation, and fostering industry-relevant competencies.